Statistics on U.S. Immigration: An Assessment of Data Needs for Future Research - National Research Council (The National Academies Press, 1996)
The growing importance of immigration in the United States today prompted this examination of the adequacy of U.S. immigration data. This volume summarizes data needs in four areas: immigration trends, assimilation and impacts, labor force issues, and family and social networks. It includes recommendations on additional sources for the data needed for program and research purposes, and new questions and refinements of questions within existing data sources to improve the understanding of immigration and immigrant trends.

Youth Development and Neighborhood Influences: Challenges and Opportunities - National Research Council (The National Academies Press, 1996)
On January 25, 1996, the Committee on Youth Development of the Board on Children, Youth, and Families convened a workshop to examine the implications of research on social settings for the design and evaluation of programs that serve youth. The January workshop provided an opportunity for the committee to examine the strengths and limitations of existing research on interactions between social settings and adolescent development. This research has drawn attention to the importance of understanding how, when, and where adolescents interact with their families, peers, and unrelated adults in settings such as home, school, places of work, and recreational sites. This workshop builds on previous work of the National Research Council and reiterates its support for integrating studies of social settings into more traditional research on individual characteristics, family functioning, and peer relationships in seeking to describe and explain adolescent behavior and youth outcomes. Not only does this report examine the strengths and limitations of research on social settings and adolescence and identify important research questions that deserve further study in developing this field, but it also explores alternative methods by which the findings of research on social settings could be better integrated into the development of youth programs and services. Specific themes include the impact of social settings on differences in developmental pathways, role expectations, and youth identity and decision-making skills, as well as factors that contribute to variations in community context.

Understanding Violence Against Women - National Research Council (The National Academies Press, 1996)
Violence against women is one factor in the growing wave of alarm about violence in American society. High-profile cases such as the O.J. Simpson trial call attention to the thousands of lesser-known but no less tragic situations in which women's lives are shattered by beatings or sexual assault. The search for solutions has highlighted not only what we know about violence against women but also what we do not know. How can we achieve the best understanding of this problem and its complex ramifications? What research efforts will yield the greatest benefit? What are the questions that must be answered? Understanding Violence Against Women presents a comprehensive overview of current knowledge and identifies four areas with the greatest potential return from a research investment by increasing the understanding of and responding to domestic violence and rape: What interventions are designed to do, whom they are reaching, and how to reach the many victims who do not seek help. Factors that put people at risk of violence and that precipitate violence, including characteristics of offenders. The scope of domestic violence and sexual assault in America and its conequences to individuals, families, and society, including costs. How to structure the study of violence against women to yield more useful knowledge. Despite the news coverage and talk shows, the real fundamental nature of violence against women remains unexplored and often misunderstood. Understanding Violence Against Women provides direction for increasing knowledge that can help ameliorate this national problem.

Careers in Science and Engineering: A Student Planning Guide to Grad School and Beyond - Institute of Medicine; National Academy of Sciences; National Academy of Engineering (The National Academies Press, 1996)
As science and technology advance, the needs of employers change, and these changes continually reshape the job market for scientists and engineers. Such shifts present challenges for students as they struggle to make well-informed education and career choices. Careers in Science and Engineering offers guidance to students on planning careers2014particularly careers in nonacademic settings2014and acquiring the education necessary to attain career goals. This booklet is designed for graduate science and engineering students currently in or soon to graduate from a university, as well as undergraduates in their third or fourth year of study who are deciding whether or not to pursue graduate education. The content has been reviewed by a number of student focus groups and an advisory committee that included students and representatives of several disciplinary societies. Careers in Science and Engineering offers advice on not only surviving but also enjoying a science- or engineering-related education and career2014how to find out about possible careers to pursue, choose a graduate school, select a research project, work with advisers, balance breadth against specialization, obtain funding, evaluate postdoctoral appointments, build skills, and more. Throughout, Careers in Science and Engineering lists resources and suggests people to interview in order to gather the information and insights needed to make good education and career choices. The booklet also offers profiles of science and engineering professionals in a variety of careers. Careers in Science and Engineering will be important to undergraduate and graduate students who have decided to pursue a career in science and engineering or related areas. It will also be of interest to faculty, counselors, and education administrators.

The Path to the Ph.D.: Measuring Graduate Attrition in the Sciences and Humanities - National Research Council (The National Academies Press, 1996)
There is a growing concern among educators and policymakers about the level of attrition from Ph.D. programs in the sciences and humanities at some U.S. universities. Reliable estimates of graduate student attrition are difficult to obtain, however, because most information comes from the administrative records of individual institutions. This book provides a summary of datasets that could be used to analyze patterns of graduate student attrition and degree completion nationally, along with an analysis of recent studies on the subject. Based on this information, the committee examines the feasibility of designing a system to produce national estimates of graduate student attrition.

Issues in Civilian Outplacement Strategies: Proceedings of a Workshop - National Research Council (The National Academies Press, 1996)
In the past six years, planned downsizing has reduced the civilian work force of the U.S. Department of Defense from over 1 million to just under 850,000. By 2001, approximately 119,000 more civilian jobs will be eliminated. The reemployment picture for civilians is not strong, and the economic impact of base closings will also be felt by the surrounding communities. This book presents creative ideas for civilian outplacement based on or suggested by private-sector experiences. It discusses a number of issues that the Department of Defense must consider in its outplacement efforts, including organizational planning for effective outplacement services, whether or not to customize services for particular types of employees, monitoring outplacement practices to learn what works, and working with local communities in providing both job search and social services.

Spotlight on Heterogeneity: The Federal Standards for Racial and Ethnic Classification (The National Academies Press, 1996)

Local Fiscal Effects of Illegal Immigration: Report of a Workshop - National Research Council (The National Academies Press, 1996)
The recent level of illegal immigration to the United States has increased debates about the effect of these immigrants on the cost of public services, and states have begun to enact policies that limit the public services available to illegal immigrants. The central issues are how many illegal immigrants reside in particular local areas and states and their effect on public expenditures and revenues and the economy in general. The Local Fiscal Effects of Illegal Immigration workshop selected six studies for analysis. The six case studies focused on one specific aspect of the complex question of the demographic, economic, and social effects of immigration: the net public services costs of illegal immigrants to selected geographical regions.

Changing Numbers, Changing Needs: American Indian Demography and Public Health - National Research Council (The National Academies Press, 1996)
The reported population of American Indians and Alaska Natives has grown rapidly over the past 20 years. These changes raise questions for the Indian Health Service and other agencies responsible for serving the American Indian population. How big is the population? What are its health care and insurance needs? This volume presents an up-to-date summary of what is known about the demography of American Indian and Alaska Native population2014their age and geographic distributions, household structure, employment, and disability and disease patterns. This information is critical for health care planners who must determine the eligible population for Indian health services and the costs of providing them. The volume will also be of interest to researchers and policymakers concerned about the future characteristics and needs of the American Indian population.

Xenotransplantation: Science, Ethics, and Public Policy - Institute of Medicine (The National Academies Press, 1996)
Xenotransplantation involves the transplantation of cells, tissues, and whole organs from one species to another. Interest in animal-to-human xenotransplants has been spurred by the continuing shortage of donated human organs and by advances in knowledge concerning the biology of organ and tissue rejection. The scientific advances and promise, however, raise complex questions that must be addressed. This book considers the scientific and medical feasibility of xenotransplantation and explores the ethical and public policy issues surrounding the possibility of renewed clinical trials. The volume focuses on the science base of xenotransplantation, public health risks of infectious disease transmission, and ethical and public policy issues, including the views of patients and their families.

Colleges of Agriculture at the Land Grant Universities: Public Service and Public Policy - National Research Council (The National Academies Press, 1996)
Since their inception in 1862, the U.S. land grant colleges have evolved to become the training ground for the nation's and the world's agriculturists. In this book, the committee examines the future of the colleges of agriculture in light of changing national priorities for the agricultural, food, and natural resource system. The effects of federal funding constraints also are examined, as are opportunities for growth presented by developments in science. The committee's preceding volume, Colleges of Agriculture at the Land Grant Universities: A Profile, is a compilation of the data that helped formulate the specific questions to be addressed. Colleges of Agriculture at the Land Grant Univerisities: Public Service and Public Policy is the deliberative report, rating conclusions and recommendations for institutional innovation and public policy. It addresses these and other questions: What education mission should colleges of agriculture adopt2014and what strategies should they use2014in light of significant changes in the agricultural complex? Research in agriculture is expected to respond to consumer demands, environmental concerns, world population growth, and increasing pressure on agricultural lands. Is the century-old structure of land grant university-based research up to the task? What is the role of extension in light of today's smaller farming communities and larger farming conglomerates? This volume is the culmination of a landmark evaluation of land grant colleges of agriculture, an American institution. This document will be of value to policymakers, administrators, and others involved in agricultural science and education.

Fetal Alcohol Syndrome: Diagnosis, Epidemiology, Prevention, and Treatment - Institute of Medicine
It sounds simple: Women who drink while pregnant may give birth to children with defects, so women should not drink during pregnancy. Yet in the 20 years since it was first described in the medical literature, fetal alcohol syndrome (FAS) has proved to be a stubborn problem, with consequences as serious as those of the more widely publicized \

The National Scholars Program: Excellence with Diversity for the Future - Program Design (The National Academies Press, 1996)

Safe, Comfortable, Attractive, and Easy to Use: Improving the Usability of Home Medical Devices (The National Academies Press, 1996)

Improving Data on America's Aging Population: Summary of a Workshop - National Research Council (The National Academies Press, 1996)
The Committee on National Statistics and the Committee on Population, at the request of the NIA, convened a workshop in March 1996 to discuss data on the aging population that address the emerging and important social, economic, and health conditions of the older population. The purposes of the workshop were to identify how the population at older ages in the next few decades will differ from the older population today, to understand the underlying causes of those changes, to anticipate future problems and policy issues, and to suggest future needs for data for research in these areas. The scope of the workshop was broader than that of the 1988 CNSTAT report, including not only data on health and long-term care, but also actuarial, economic, demographic, housing, and epidemiological data needs for informing public policy.

Using Performance Monitoring to Improve Community Health: Conceptual Framework and Community Experience - Institute of Medicine (The National Academies Press, 1996)

Reproductive Health Interventions: Report of a Meeting (The National Academies Press, 1996)

The Role of Scientists in the Professional Development of Science Teachers - National Research Council
Scientists nationwide are showing greater interest in contributing to the reform of science education, yet many do not know how to begin. This highly readable book serves as a guide for those scientists interested in working on the professional development of K-12 science teachers. Based on information from over 180 professional development programs for science teachers, the volume addresses what kinds of activities work and why. Included are useful examples of programs focusing on issues of content and process in science teaching. The authors present \

(NAS Colloquium) Science, Technology and the Economy (The National Academies Press, 1996)

Improving America's Schools: The Role of Incentives - National Research Council
Reform of American education is largely motivated by concerns about our economic competitiveness and American's standard of living. Yet, few if any of the public school reform agendas incorporate economic principles or research findings. Improving America's Schools explores how education and economic research can help produce, in the words of Harvard's Dale W. Jorgenson, \